On the cyclical movement in John Keats's "to autumn". Issue 3 (3rd July 2021) - Duan, Yingjie
Abstract: Keats's "To Autumn, " a short poem dedicated to the season of autumn, implicitly exhibits the cyclical movement of one day and four seasons, manifesting Northrop Frye's definition of "process of life." As the speaker's focus shifts from autumnal fruitfulness to autumnal labor and to autumnal sound, there is also an implicit progression from morning to afternoon and into dusk. Parallel to the diurnal cycle within the poem, there is a transition from early autumn to mid-autumn and then to the heralding of winter. The cycles of one day and four seasons epitomize the single great circle of life in general.